Exploring the role of the digital economy in supporting the growth of the halal Small and Medium-sized Enterprise (SME) sector - Novi Primita Sari; Supiandi Supiandi (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — In light of Malang City's significant Muslim community and increased digital technology adoption during the COVID-19 pandemic, this study explores the impact of digital platforms on micro and small businesses.Method — This research employs a descriptive quantitative approach, combining a literature review with questionnaire-based primary data collection. The gathered data is subsequently analyzed.Result — Utilizing the smart PLS 3 application, we find that two of the three latent variables significantly influence variable Y. Specifically, Perceived Usefulness (represented by X1) and Perceived Ease of Use (represented by X3) have a notable impact on Y. This impact is reflected in the increased total transactions facilitated by micro, small, and medium enterprises (MSMEs) through the use of digital economic tools.Contribution — This research introduces a unique perspective by highlighting how digital platforms support the halal industry. The integration of digital innovation requires alignment with the needs and scale of MSMEs. While these innovations offer significant advantages, MSMEs must also address technical challenges, data security concerns, and potential shifts in business practices resulting from the adoption of new technologies.